Temporal Variability of the Batumi Delta Wetlands - Bülent Turgut (Doğal Afetler ve Çevre Dergisi, 2023)
Wetlands are invaluable ecosystems as they provide important services, but these areas are rapidly degrading due to anthropogenic pressures and natural changes/transformations. It is thought that this negative change will increase in the upcoming period due to the climate change and the rising demand for soil and water. Determining the changes in wetlands is very important in terms of management planning of these areas. NDWI (Normalized Difference Water Index) is a widely used method for determining the hydrological characteristics of wetlands. This study was carried out to determine the temporal variability of wetlands in the Batumi Delta and the relationship of this change with basic climate parameters such as average temperature and total precipitation. For this purpose, the average temperature and total precipitation amount of the months of April, May, June, July, August, and September in the period between 2016-2021 of the study area and the NDWI values of these time periods were determined. Green and NIR bands of Sentinel2 satellite images were used to determine NDWI values. QGIS software was used to process satellite images, and ArcGIS software was used to determine and map NDWI values. As a result of the study, it was seen that NDWI values changed by months and years, and the temperature was more effective than precipitation on this change.